Regional output differences in international perspective - Bettina Aten; Alan Heston (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
Accurate regional estimates of output are desired as an indicator of level of development and as a variable used to explain internal migration, demand patterns, fertility and other aspects of behaviour. This chapter explores one often neglected aspect of regional income differences, namely that due to price differences or regional purchasing power parities. When nominal regional income measures are adjusted for these price level differences they are termed real regional incomes. The preferred method of estimating regional purchasing power parities by detailed price comparisons is discussed for Brazil, the United States and the European Union. The empirical thrust of the chapter is an investigation of different methods for estimating regional real incomes based on PPP data for 167 countries and nominal regional incomes and other data for about 870 administrative areas at the subnational level. Even in their present form we believe the real income estimates provided for the geographical units present opportunities for understanding the world economic structure.
Keywords: C2; R1; 330; purchasing power parities; regional price levels; spatial models; Kaufkraftparität; Regionale Preisstruktur; Raumwirtschaftstheorie; Welt